¿La maría o maría?: el uso del artículo determinado + antropónimo en el habla de Loja, Ecuador. - Sandoval Jarro, Brayan Daniel (2022)
In the present investigation, the use of the definite article + anthroponym construction in Loja speakers is analyzed, taking into account both the sector (urban and rural) and the sex (male and female) in allusion to the receiver with the aim of analyzing the use of this construction in the vernacular speech of the Lojanos. To carry out the stated objective, a field research with a qualitative approach and a descriptive - explanatory scope was chosen with spontaneous interviews without the need for a previous script, also called unstructured. To obtain the pertinent data, the corpus of the National University of Loja was used, carried out through the project entitled Spoken Castilian in Loja (1940-2019): diatopic, diastratic and diaphasic approach. Among the most pertinent results, a slight predominance of this use in the urban area compared to the rural area stands out, which contradicts the belief that it is a use confined to rural areas. An existing affective value is also perceived in the dialogues of the informants when using the aforementioned structure to refer to their relatives, neighbors and friends. On the other hand, the structure definite article + anthroponym is used with a clear preponderance to designate feminine proper names and attempts are made to avoid masculine anthroponyms, this is evident in numerous dialogues.